CYBER SECURITY POLICIES OF TURKIYE AND ENGLAND DURING THE PANDEMIC PERIOD - ÜNVER, Gül Nazik (Cyberpolitik Journal, 2023)
The World Health Organization (WHO), which officially announced global health emergency in January 2020, declared that the COVID-19 outbreak was a pandemic by 11 March. Since then, the pandemic has become global. The pandemic spread rapidly between countries and affected almost every community in many ways. This shows that it especially affects politics, economy, health, culture, education and technology. This study claims that the policy and strategy, economic sector, health sector, education and training and technologies of Türkiye and England were adversely affected during the pandemic period and that countries developed cyber security policies for these elements. This study highlights that lockdowns, quarantines and other preventive measures have far-reaching effects on the political and economic well-being of countries around the world, including Türkiye and England. In addition, this study analyzes and provides an overview of the Turkish and British governments’ response to COVID-19 in terms of cybersecurity policies, in order to demonstrate the far-reaching and potentially long-term consequences of the virus on the future of countries.